CHEMICAL INVESTIGATION OF ESSENTIAL OIL OF POLYGONATUM VERTICILLATUM (LILIACEAE) - P.S. Rajpoot (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2010)
Polygonatum Verticillatum (Liliaceae) is an erect glabrous natural herb growing at an altitude of 9000-12500 ft. of Kumaon Himalayan Mountains in Uttaranchal, India. The root stock of the plant is sweet, cooling, emollient, diuretic, aphrodisial, galactagogal, aspestising. The plant belongs to Astvag group medicinal Plants rhyzomes used is as an ingredient of Chyvanprash and an important Ayurvedic tonic